Natural gas industry in China: Development situation and prospect - Jian Li; Yuanqi She; Yang Gao; Mingpeng Li; Guiru Yang; Yanjun Shi (Natural Gas Industry B, 2020)
China's natural gas industry has entered a rapid development stage, and its supply, sales, storage and transport systems are continuously undergoing profound structural change. It is a major issue concerning national energy security to objectively grasp the current development situation and trend of natural gas industry and make scientific predictions. In this regard, through the analysis of global natural gas resources status, trade pattern and development trend, we reviewed the development process, current situation, trend and problems in natural gas industry in China, then made prospect analysis and judgment in terms of demand and supply, etc., and finally put forward some reasonable and sustainable strategic countermeasures and proposals. The following results were obtained. (1) The comprehensive energy elasticity coefficient method was adopted to predict that the natural gas consumption volume in 2030 will be about 650 billion cubic meters. (2) Affected by many factors such as energy supply side reform, industrialization and urbanization, the growth rate of domestic natural gas consumption is much higher than that of production and the development of natural gas industry still faces a series of problems. (3) It is necessary to strengthen the exploration and development of natural gas to ensure the increase of domestic natural gas storage and production. (4) Diversified import channels should be continuously expanded to disperse the risk of excessive growth of natural gas dependence on foreign countries. (5) The construction of national and dynamic interconnection system and hub should be accelerated. (6) China should rationalize the price mechanism of natural gas, gradually open the control on industrial and seasonal consumption, and strengthen the overall sales guidance in the national market.